A simplified model for drag evaluation of a streamlined body with leading-edge damage. Issue 10 (3rd October 2021) - Yu, Haoliang; Ciri, Umberto; Malik, Arif; Leonardi, Stefano
Abstract : A reduced-order model (ROM) is proposed for efficient drag prediction on a streamlined body with surface imperfections that emulate leading-edge roughness or erosion-induced damage. Surface imperfections are idealised as forward-facing step(s) for which the chordwise position, spanwise length, and distribution of steps are varied. It is hypothesised that superposed a bilinear dependencies on the chordwise location and spanwise length of individual steps comprising the damage provide for reasonable ROM predictions of the corresponding change in total drag on the streamlined body. Direct numerical simulations are applied to test the ROM hypotheses and to study interactions between the three-dimensional steps and the separated near-wall turbulent flow fields, justifying the underlying terms and form of the ROM. Insights into the flow physics influencing both form and friction contributions to total drag are revealed, and satisfactory model performance is demonstrated for complex damage idealisations that emulate fracture of laminated wind turbine blades.